(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Patients presenting with BIMC are relatively rare and the aim of the Orthodontist is to create a dentition that is functionally and aesthetically acceptable. The BIMC may result in altered facial appearance with malocclusion and psychological distress in some individuals. Case presentation: The present case report describes a 17-year-old female patient with nonsyndromic, BIMC. Clinical and CBCT examinations revealed BIMC. Following open surgical exposure treatment planning, the patient was treated with orthodontic fixed mechanotherapy to correct BIMC and other problems. Slow force mechanics with passive self-ligating MBT 0.022 orthodontic braces were used. Results: Open surgical exposure and active orthodontic treatment was completed in 18 months. The management of BIMC requires multidisciplinary approach to achieve better aesthetics and improved occlusal function. Conclusion: A combined Open Surgical Exposure-Orthodontic Traction-Orthodontic treatment would help achieve desired aesthetics and functioning occlusion. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.169-173